INCLUSIVE EPISTEMOLOGY: A SYNTHESIS OF AL-GHAZALI AND FAZLUR RAHMAN FOR A MODERN ISLAMIC CURRICULUM - Ami, Lasmi Anisa Putri; Samad, Duski; ST. Mamad, Firdaus (Majalah Ilmiah Tabuah: Ta`limat, Budaya, Agama dan Humaniora, 2025)
Amid the challenges of globalization and the digital age, Islamic education faces a profound crisis: how to weave classical spiritual heritage with the imperative for modern inclusivity. This context motivates an innovative exploration synthesizing Al-Ghazali's epistemology, which integrates irfani (intuitive) and rational dimensions, with Fazlur Rahman's contextual hermeneutical approach. The primary goal is to establish an inclusive epistemology as a robust foundation for a modern Islamic curriculum, achieved through a deep comparative analysis of both thinkers' ideas, aimed at developing a pedagogy that embraces diversity, critical thinking, and humanistic values within pluralistic societies like Indonesia. Employing a qualitative method based on library research and descriptive-analytic comparative analysis, this study examines primary sources, including Al-Ghazali's Ihya Ulum al-Din and Fazlur Rahman's Islam and Modernity, triangulated with secondary literature on knowledge integration. The synthesis yields an inclusive curricular framework that unites textual, rational, and intuitive dimensions. This framework is highly relevant for reforming Islamic Religious Education (PAI) through models based on Qur'anic justice, fostering a generation adaptive to contemporary issues. This research's core contribution is bridging the gap between tradition and innovation, thereby promoting a more vibrant, inclusive, and globally competitive Islamic education.